A blended learning model with IoT-based technology: Effectively used when the COVID-19 pandemic? - Siripongdee, Kobchai; Pimdee, Paitoon; Tuntiwongwanich, Somkiat (My University, 2020)
IoT-based technology was considered to refer to all heterogeneous objects and devices through any networks, and Blended Learning (BL) is the educational approach to combine face-to-face (F2F) instruction with ICT instruction. In this COVID-19 pandemic, a model of BL with IoT-based maybe the best New Normal solution for all educational stakeholders. While Traditional F2F is forced to change by social distancing to prevent COVID-19. Many IoT-based "things" could be added in class to create and improve a smart learning environment while portable devices could be joined for the learning goals. This study divided BL into 4 characteristics; F2F, Self-paced, Tele-D, and Ubiquitous, which were further categorized into 3 typical cases of learning environments, Digital, Embedded, and Side-by-side cases. Content analysis method was used to analyze and synthesize a model from related literatures, textbooks, research, articles and websites. A framework of this model has 2 roles of user interfaces (teacher and student) which link 6 modules and a set of databases and 2 types of contexts (classroom and personal).
Keywords: Blended learning; Educational technology; IoT-based technology